Precipitating factors of heart failure in adults at the Military Hospital, Asunción 2023 - Real-Delor, Raúl E. (2024)
Objective: to describe the demographic and clinical characteristics and determine the precipitating factors of heart failure. The importance of knowing these factors will allow measures to be applied that prevent or delay cardiac decompensation. Methods: we perform an observational, descriptive, cross-sectional study design was applied. The sample was made up of men and women, of legal age, who were admitted to the Medical Clinic Service for decompensated heart failure between April and October 2023. A sampling of consecutive cases was used, and demographic and clinical variables were measured. Descriptive statistics were applied. The study was approved by the Ethics Committee of the Universidad Privada del Este, Paraguay. Results: the sample consisted of 130 subjects, 65 being men with a mean age of 64 ± 16 years and 65 women with a mean age of 62 ± 15 years. The most frequent comorbidities were arterial hypertension (93.8%) and diabetes mellitus (56.9%). The predominant functional grades were III (36.1%) and IV (25%). The NT-proBNP value was found to be elevated especially in functional grade IV (median 3138 pg/mL). The causes of decompensation were various in the same patient and were predominated by hypertensive crisis (71.4%), excessive intake of water and salt (64.6%) and acute coronary syndrome (51.5%). The mortality was 0.78%. Conclusions: the main causes of heart failure decompensation were modifiable factors: hypertensive crisis, lack of adherence to diet and acute coronary syndrome. It is recommended to apply preventive measures based on these data, since they are reversible.